Identification of novel functional mini-receptors by combinatorial screening of split-WW domains [research data] - Thomas, Franziska; Neitz, Hermann; Paul, Niels Benjamin; Häge, Florian; Lindner, Christina; Graebner, Roman; Kovermann, Michael (Universität, 2023)
β-Sheet motifs such as the WW domain are increasingly being explored as building blocks for synthetic biological applications. Since the sequence-s...
Gesehen am 13.02.2023
Keywords: Forschungsdaten; Datenbank